Ghani Format Learning Method (GFLM) helps memorizing difficult facts - Siti Sarah, Mohamad Rajimi (2017)
More than 300 PT3 and SPM candidates from Pekan and Kuantan gettting the opportunity to learn note taking skill from Ghani Format Learning Method (GFLM).